OPTIMIZATION OF INTRANASAL COVID-19 VACCINE FORMULATION WITH Lactococcus lactis pNZ HCR BACTERIA AS VECTOR IN LIQUID AEROSOL PREPARATION - Valentina Yurina (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Vaccination is an effective method to suppress COVID-19 transmission, but injection-based vaccination is less effective due to its inability to induce mucosal immunity. This study aimed to determine the effects of vaccine formulations on bacteria viability and antigen expression to find the optimal formulation. Three intranasal preparation formulations (F1, F2, and F3) were created with different ingredient compositions, along with a control. Physicochemical tests were conducted on day 0 and day 14 to assess bacterial viability, and antigen expression was evaluated using the western blot method. Formula 2, containing sodium alginate (0.615%), trehalose (4.125%), polyvinyl alcohol (0.1%), and calcium chloride (5%), exhibited the best viability test results, although no significant differences were observed among the groups. The study concluded that variations in composition concentrations could affect bacterial stability, with Formula 2 showing the best results in terms of bacteria viability and antigen expression up to 14 days after formulation.